HubunganTriple Helix, Inovasi, Keunggulan Bersaing dan Kinerja - Asyhari -; Wasitowati - (Conference In Business, Accounting, And Management (CBAM), 2015)
Creative industries have a large enough contribution to the development of the national economy, particularly employment and raise incomes masyarakat.Permasalahan facing the creative industries are still many, especially the ability to innovate and the competitiveness is still weak, so the impact on performance. This study aims to examine the role of the Triple Helix (intellectual, government, business) to improve innovation capability and competitive advantage creative industry. The total sample of 115 respondents were focused on craft and fashion sector in Central Java, as well as methods of sampling using purposive sampling, the data obtained will be processed using the program Partial Least Square (PLS). The results showed three actors Triple Helix (intellectual, government, business) significantly affects the ability of innovation and competitive advantage. Likewise, innovation and competitive advantage are also significant effect on performance. Keywords: Triple Helix, Innovation, Competitive Advantage, Performance